Развитие жирового тела у преимагинальных стадий мухи комнатной— Musca domestica L. (Diptera, Muscidae) - Карпенко, Л.В. (Вестник зоологии, 1972)
The fatty body of Musca domestica L. consists of two formations different in origin, structure and partially, in functions: uninuclear larvae and binuclear imaginal fatty cells. In the larvae of the I age reserve substances in a form of fatty drops are not accumulated. Only after the second moult the number and size of fatty vacuoles increases rapidly. During nutrition of a larvae the size of trophocytes increases from age to age. Not long before cessation of nutrition glycogen is accumulated in the trophocytes. In a prepupa a new type of inclusions small protein-glycogen granules appear. Reserves of the fatty body in pupae are presented by big fatty-glycogen granules, small protein-glycogen gra¬nules, cytoplasm glycogen and a small number of fatty drops. Cells of the imaginal fatty body, anlages of which are met even in larvae in the second part of the pupa development period are between the larva trophocytes. Some days before imago appearance the beginning of their functioning may be established: fat and glycogen appear and then are -accumulated in them.